Natural sliced wood veneer as a universal porous lightweight substrate for supercapacitor electrode materials. Issue 86 (30th November 2017) - Lyu, Shaoyi; Chen, Yanping; Han, Shenjie; Guo, Limin; Yang, Na; Wang, Siqun
Abstract : We herein report the use of natural sliced wood veneer as a porous lightweight substrate for supercapacitor electrodes, where PANI/RGO and PPy/RGO were employed as active materials, and both wood electrodes showed good electrochemical performance. Abstract : We herein report the use of natural sliced wood veneer as a porous lightweight substrate for supercapacitor composite electrodes, where polyaniline/reduced graphene oxide (PANI/RGO) and polypyrrole/reduced graphene oxide (PPy/RGO) were employed as the complex electroactive materials, and were prepared using physical deposition and in situ polymerisation methods. Owing to the hierarchical cellular structure, penetrating channels, and hydrophilic character of the natural wood substrate, both wood electrodes displayed unique morphologies and exhibited high specific capacitances, good capacitance retention, and good cycling stabilities. More specifically, the as-designed PANI/RGO wood and PPy/RGO wood electrodes gave high gravimetric specific capacitances of 931.92 and 848.01 F g −1, respectively, at a current density of 2.5 mA cm −2 in a three-electrode test. In addition, the assembled symmetric supercapacitors showed good areal specific capacitances of 0.89 and 0.78 F cm −2, respectively, at a sweep rate of 1 mV s −1 in addition to high areal specific energies of 107.70 and 86.96 mW h cm −2, respectively, at an areal specific power of 0.25 mW cm −2 . Our results indicate that the use of natural wood as a substrate for supercapacitor electrodes will be an important contribution to the development of green and renewable energy storage devices.